SY2.5. Balance and gait assessment. Issue 8 (August 2021) - Mak, Margaret
Abstract : Postural instability and walking difficulties are the most disabling symptoms in Parkinson disease (PD), leading to falls, physical injuries, functional decline and early institutionalization. Medical, surgical and rehabilitation are the mainstay of management for balance and gait disorders. Evaluation of balance and gait disorders is crucial to determine the problems of the patients so that targeted treatment can be given. Postural instability manifests as reductions in limits of stability, postural adjustment, and postural responses. Gait disorders comprise reduced gait speed, short stride length, freezing of gait, and dual-task deficits. Postural instability and gait disorders can be evaluated using reliable and validated clinical tests, measurement scales, questionnaires and technological equipment. Objective clinical tests and measurement scales require simple equipment and needs a short time to complete the tests. Questionnaires are useful to reflect patients' perceived balance and gait ability. Technological equipment can be costly but they can increase the measurement sensitivity. The clinical tests used to evaluate postural instability include retropulsion tests, Functional reach test, and one-leg-stance test, whilst those for gait disorders include single or dual-task walk test, timed-up-and-go-test, and 6-minute walk test. Measurement scales including Berg's balance scale, mini-Balance evaluation system test and Tinetti mobility test, are used to assess overall balance and gait limitations. Most of the measurement scales have cut-off scores for predicting fall risk. Validated questionnaires such as Activities-specific balance confidence scale and Fall efficacy scale evaluate one's perceived level of balance confidence. Freezing-of-gait questionnaire subjectively assess the severity of freezing of gait. Most of the technological equipment are bulky, laboratory-based and may require a long time to complete the test and/or to analysis the data. Nowadays, body worn sensors is getting more popular because they allow measurement to be taken anywhere including patients' home and in the community. Algorithm has been built in some systems to shorten the data analyzing time. There are many choices of outcome measures and clinicians/researchers can choose the evaluation methods that is best for their measurement purposes.